Dietary knowledge and management practices of gestational diabetes mellitus among pregnant women attending ante-natal clinic at the University of Port Harcourt Teaching Hospital, Rivers State, Nigeria - Ofoezie, Chisimdindu Goodness; Tobin-West, Ibiene Charles (World Nutrition, 2025)
BackgroundGestational diabetes mellitus (GDM) is of public health significance, especially because it predisposes both the mother and child to type 2 diabetes mellitus and obesity. Adequate dietary knowledge, when translated into appropriate management practices, has been shown to reduce the burden of GDM.ObjectiveThis study assessed the level of dietary knowledge and management practices among women with gestational diabetes mellitus attending an antenatal clinic at a tertiary hospital in Nigeria.MethodsA descriptive cross-sectional design was employed. Convenience sampling was used to recruit 200 women with GDM. Data were collected using interviewer-administered questionnaires. Responses were analysed using the Statistical Package for the Social Sciences (SPSS), employing descriptive statistics and bivariate analyses to explore associations.ResultsOverall, 47% of the participants demonstrated good dietary knowledge, while 46.0% reported poor dietary management practices. Dietary knowledge was significantly associated with management practices (p = 0.032). No significant associations were observed with sociodemographic variables.ConclusionsThis study reveals gaps in dietary knowledge and management practices among women with GDM at a tertiary hospital in Nigeria. Knowledge was positively associated with practice, underscoring the need to strengthen nutrition education. Enhancing family support and ensuring the affordability, availability, and accessibility of recommended diets may improve dietary practices and contribute to more effective GDM management.